2022
DOI: 10.1161/hypertensionaha.122.19269
|View full text |Cite
|
Sign up to set email alerts
|

Day to Day Blood Pressure Variability Associated With Cerebral Arterial Dilation and White Matter Hyperintensity

Abstract: Background: Previous studies suggested blood pressure variability (BPV) might help reveal interactions between blood pressure fluctuation and white matter lesions, and the impact of elevated BPV on white matter hyperintensity (WMH) or cerebral arterial dilation is unclear. Methods: This retrospective observational study involved 2634 stroke-free individuals (68.6±11.1 years, 50.3% female), who underwent magnetic resonance imaging and magnetic resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
0
20
1
Order By: Relevance
“…This association seemed to be independent of demographic, clinical and assessment characteristics [310]. Increased BP variability (day-to-day measurements) may also play a role [311], as well as orthostatic hypotension in older people [300]. In clinical studies, long-term elevated SBP and pulse pressure incognitivelyhealthyadults aged 50 years or older was clearlyassociatedwith subsequent cognitive decline and dementia [312].…”
Section: Hmod In the Brainmentioning
confidence: 98%
“…This association seemed to be independent of demographic, clinical and assessment characteristics [310]. Increased BP variability (day-to-day measurements) may also play a role [311], as well as orthostatic hypotension in older people [300]. In clinical studies, long-term elevated SBP and pulse pressure incognitivelyhealthyadults aged 50 years or older was clearlyassociatedwith subsequent cognitive decline and dementia [312].…”
Section: Hmod In the Brainmentioning
confidence: 98%
“…In the Chinese residents in Pu-Li town and Kinmen county, Taiwan, average real variability (ARV) index recorded on a short period added significant prognostic information ( Hsu et al, 2016 ). BPV is also associated with cerebral white matter hyperintensity and might be one of the pathophysiological phenomena involving in the small vessel disease independent of hypertension ( Zhang et al, 2022 ). The Hisayama study showed that increased day-to-day BPV is, independently of average home blood pressure, a significant risk factor for the development of all-cause dementia ( Oishi et al, 2017 ).…”
Section: Autonomic Nervous System As a Predictor For Stroke Occurrencementioning
confidence: 99%
“…Besides, poor blood pressure control might also increase blood pressure variability, which has been suggested to exhibit adverse impact on the cerebrovascular system and increase the risk of stroke. 41,42 In addition, this study utilized hr-VW-MRI to assess the associations of intracranial plaque morphologies with stroke recurrence and has demonstrated that a larger MLA was associated with a lower risk of recurrent ischemic events. In alignment with previous studies, a smaller lumen area of the middle cerebral artery might imply an increased risk of first-ever stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, poor blood pressure control might also increase blood pressure variability, which has been suggested to exhibit adverse impact on the cerebrovascular system and increase the risk of stroke. 41,42…”
Section: Discussionmentioning
confidence: 99%